1997
DOI: 10.1097/00005537-199712000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Bone Resistance of the Sphenoid and Ethmoid Sinuses

Abstract: Functional endoscopic sinus surgery can be associated with iatrogenic complications. Some anatomical structures have been identified this clinically as specific danger sites. The aim of this study was to confirm and to compare these clinical data with measurements of the bone resistance of the sphenoid and ethmoid walls and to point out regions that have increased bony fragility. Critical dynamometric evaluation of the resistance to breakage of these bony structures was made on 21 anatomic specimens. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…Wagner et al 8 bilaterally measured five formalin-fixed heads, using a torque sensor mounted on an endoscope to perform osteotomies. Waridel et al 9 published results on 21 sectioned specimens preserved in 40% ethanol. A dynamometer was used to measure breaking force perpendicular to the osteotomy site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wagner et al 8 bilaterally measured five formalin-fixed heads, using a torque sensor mounted on an endoscope to perform osteotomies. Waridel et al 9 published results on 21 sectioned specimens preserved in 40% ethanol. A dynamometer was used to measure breaking force perpendicular to the osteotomy site.…”
Section: Discussionmentioning
confidence: 99%
“…Two previous studies 8,9 have shown forces ranging between 2 and 12 N are needed to breach ethmoid bone but neither of these studies were performed using surgical instruments. The aim of the current study is to investigate the magnitude of the axial forces exerted when punch osteotomies are performed within the paranasal sinuses and surrounding structures during ESS.…”
mentioning
confidence: 99%
“…As robotic technology matures, the automation of endoscopic sinus procedures 1,7 and other otorhinolaryngological surgical procedures 8 can already be envisioned. To design a control system for a robotic application to undertake sinus surgery, our knowledge of the anatomy and material properties of the paranasal sinus system has to be formalized.…”
Section: Discussionmentioning
confidence: 99%
“…This has led to attempts to objectively quantify the forces required to fracture paranasal sinus lamella. 13 …”
mentioning
confidence: 99%
“…Although extensive descriptive anatomic data regarding the surgical anatomy of the paranasal sinuses are available today, 13,14 only limited information on the bony walls of the paranasal sinuses (e.g., bone density or bone resistance, for understanding complications related to ESS) can be found in the literature 15,16 . Up to the present, there have been no reports on the application of bone density measurements on plastinated specimens in the field of rhinology.…”
Section: Introductionmentioning
confidence: 99%